(3eMGSHI GdJcGdja (B:s (3eONd EOGQj (B/s - (3ghQfLQf, JTGQdRs; (3OGJGQ, SQjcGfJ s; (3ahSJQ, LhQL s ((3GdQjGV(B: s (3OGQ GdeQjN ddfTQ(B, s, 1996)
(3OhQ GdeMGSH aj GdJfXje(B-(3ebOeI aj eUWdMGJ hCZQGV GdJcdaI(B-(3YdGbGJ GdJcdaI(B((3GdMLe,GdQHM(B)-(3fXGe JMOjO GdJcdaI aj bWGY GdefTBJ GdNOejI hGdefTBJ GdJLGQjI(B-(3fXe JMOjO GdJcdaI aj bWGY GdefTBI GdUfGYjI(B-(3GdehGRfI GdTGedI heMGSHI GdeSFhdjI(B-(3GdehGRfGJ GdeQfI hGdEfMQGaGJ hQbGHI GdEOGQI(B-(3CKQ WQb JMOjO JcdaI(B((3GdeNRhf HOjdg Ydi GdONd(B)-(3JMOHO Sdhc GdJcGdja(B-(3GdedGFeI hGdJcGdja hYedjI GJNGP GdbQGQ(B-(3bQGQGJ GdJSYjQ,hbQGQGJ QHMjI GdefJL,hEOGQI GdJcdaI(B-(3fXe QbGHI GdEOGQIs
Keywords: (3GdeMGSHIs; (3eMGSHI GdJcGdjas